An Assessment Of The Relationship Between Motivation And Teachers’ Job Mobility In Ondo State, Nigeria - Osalusi, F. M.; Onipede, A. A. (Advances in Social Sciences Research Journal, 2017)
This paper investigated the relationship between motivation and teachers’ job mobility in Ondo State, Nigeria. The study adopted a descriptive research of the survey type. The population consisted of all teachers of public secondary schools in Ondo State. Multi-stage sampling procedures were used to select the sample for the study. Stage one involved the use of simple random sampling technique to select 5 Local Government Areas from the 18 Local Government Areas in the State. The second stage involved the selection of 10 public secondary schools using purposive random sampling technique. 50 teachers were selected from each of the public schools using simple random sampling technique at third stage to make a total of 500 teachers as sample for the study. The content of the instrument was validated by relevant experts. The reliability was ascertained through test- retest method and Cronbach Alpha reliability coefficient method was used to determine the internal consistency of the items. The result yielded reliability coefficient of 0.87. Data collected were analyzed using descriptive and inferential statistics. Frequency counts, mean scores, percentages were used to answer questions raised while Pearson’s Product Moment Correlation and t-test were used to test the hypothesis at 0.05 level of significance. The study revealed that the level of teachers’ job mobility was low and that motivational issues have a very high impact on teachers’ job mobility. It was therefore recommended among others that Government at all levels and education stakeholders should encourage teachers to be committed to their jobs by providing necessary conducive environments and incentives to ensure better performance for national development.